Effects of two typical quinolone antibiotics in the marine environment on Skeletonema costatum - Lin, Yuxin; Li, Tiejun; Zhang, Yurong (Frontiers in Marine Science, 2024)
This study investigated the effects of levofloxacin (LEV) and norfloxacin (NOR) on Skeletonema costatum, focusing on cell growth, chlorophyll a (Chla) content, maximal quantum yield of PSII (Fv/Fm), protein content, enzyme activities of superoxide dismutase (SOD), glutathione reductase (GR), and glutathione peroxidase (GSH-PX), and the membrane lipid peroxidation product malondialdehyde (MDA) content were conducted to analyze the responses of S. costatum under LEV and NOR exposure. Cell growth, Chla content, Fv/Fm, protein content, enzyme activities, and MDA content were assessed to elucidate physiological changes. Both LEV and NOR inhibited S. costatum growth, except for 10 mg/L NOR, which promoted growth. Algal cells exhibited higher sensitivity to LEV, with 96h-IC50 values of 14.770 mg/L for LEV and 44.250 mg/L for NOR. Low NOR concentration (10 mg/L) increased Chla content, while high antibiotic concentrations (>20 mg/L for LEV, >100 mg/L for NOR) decreased Chla content and Fv/Fm, indicating an impact on photosynthesis. Elevated LEV and NOR levels reduced protein and MDA content but increased GR, SOD, and GSH activities, indicating induced oxidative stress. The study provides a comprehensive analysis of LEV and NOR effects on marine microalgae growth and underlying physiological mechanisms, shedding light on potential ecological risks posed by antibiotics in marine ecosystems.